Social Cognition and Theory of Mind - Miray Atacan Yaşgüçlükal; Ayşe Deniz Elmalı; Barış Korkmaz (Neuropsychiatric Investigation)
For an individual to exist in a society, they must be receptive to not only signals from their natural environment but also to those from their social environment. Therefore, the human brain possesses a social cognition capable of processing, interpreting, and responding to various signals related to social interaction and relationships. Considering the prevalence of social dysfunction in neurological disorders, social cognition should now be recognized as a core area of function requiring clinical attention.